Ethnomathematical exploration of the “Ompangan” tradition of the Jember Madura community - Wahyuni, Indah; Apriyono, Fikri; Anggriani, Dita Loka (SAINTIS Publishing, 2023)
Culture is closely related to the lives of Indonesian people, in the current era of technological sophistication, culture is one of the means to study science, one of which is ethnomathematics. Ethnomathematics is a branch of mathematics that uses culture as a means to deepen the knowledge and concepts of mathematics education through the role of culture in society. This study focuses on the ethnomathematical exploration of the “ompangan” tradition of the Jember Madura community in Kalisat with the aim of describing ethnomathematics in the ompangan tradition of the community and formulating the concept of mathematical calculations. This research took place at Jalan Diponegoro Dusun Krajan 1 RT/RW 012/004 Glagahwero Kalisat. This study uses a qualitative method with a descriptive approach, with data collection techniques through interviews and observations. The results showed that the ompangan culture contained mathematical concepts in it that linked culture to the mathematical counting process, namely the concept of worth comparison and a system of linear equations used to determine the number of goods with the same price or value.